The Polygamy Concept in the Qur'an Perspective - Abdullah, Abdullah; Lala, Andi (Universitas Islam Sultan Agung, 2023)
Polygamy, the marriage practice in which a man has more than one wife, has become a controversial topic debated in various societies, including in the context of religious teachings. This research aims to explore the Qur'anic perspective on polygamy and its implications for Muslim individuals, families, and communities. Through analysis of verses from the Qur'an relating to polygamy, this research highlights the legal aspects, conditions, and objectives of this practice within the framework of Islamic values. The research results show that the Qur'an permits polygamy with strict provisions, emphasizing the need for fair treatment of the wives one has. Although the Qur'an gives permission, this research emphasizes that polygamy should not be considered as a primary option, but rather as a last solution in certain circumstances. By highlighting the moral and social responsibilities inherent in men who choose polygamy, the Qur'an emphasizes the importance of maintaining balance and justice in domestic life. This study contributes to a deeper understanding of the Qur'anic view of polygamy, discussing the dimensions of ethics, justice, and responsibility in the context of the Islamic family and society. Thus, this research seeks to present a richer view of polygamy as a complex aspect of life, embodied in deep Islamic values.